A strategy for improving the mechanical properties of silk fiber by directly injection of ferric ions into silkworm. (15th May 2018) - Liu, Qingsong; Wang, Xin; Tan, Xiaoyin; Xie, Xiaoqian; Li, Yi; Zhao, Ping; Xia, Qingyou
Abstract: Silk fibers produced by the silkworm, Bombyx mori, are widely used bio-materials due to their superior toughness and elongation. However, the stress and stiffness of silkworm silk are not comparable to the synthetic fiber or other natural silk such as the spider silk. How to improve the mechanical properties of silk fibers has been of great interest. In this paper, we developed a new strategy for improving the mechanical properties of silk fibers by directly injecting ferric ions (Fe 3+ ) into silkworm. The Fe 3+ -injected silkworms could produce robust silk fibers with improved stress, stiffness and toughness. Secondary structural analysis indicated that Fe 3+ promoted the conformation transition of silk from random coil or helical structure to β-sheet structure. These evidences might explain why these fibers became stronger, stiffer and tougher. Trying to unravel the molecular foundation behind this interesting phenomenon, turbidity assays and fluorescence spectroscopy were introduced. The results indicated that Fe 3+ was able to interact with tyrosine and tryptophan residues within the silk. The crosslinking might act as the "bridge" to form the β-sheet structure, thus increasing the mechanical properties of silk fiber. These findings suggested that Fe 3+ could be a promising target to modify the mechanical properties of silk fibers. Graphical abstract: Unlabelled Image Highlights: We reported a new strategy for modifying the mechanical properties of silk fibers. Injection of Fe 3+ improved the mechanical properties of silk fibers. Fe 3+ induces the conformational transition of silk via interacting with tyrosine and tryptophan.